Platelet Reactivity In Vitro in Relation to Thromboxane in Healthy Pregnancy - Horn, E H; Hardy, E; Cooper, J; Heptinstall, S; Rubin, P C (Thrombosis and Haemostasis, 1996)
There is substantial evidence of increased platelet reactivity in vivo and in vitro during pregnancy. Previous in vitro studies suggest that platelets from pregnant women show increased sensitivity to agonists, the response to which has a thromboxane dependent component. The aim of this study was to determine whether this is due to increased activity of the thromboxane biosynthetic pathway or to increased platelet sensitivity to the effects of thromboxane. During pregnancy, platelets were more sensitive to the pro-aggregatory effects in vitro of the thromboxane mimetic U46619, in whole blood and in platelet rich plasma, compared to those from non-pregnant controls. The difference in extent of U46619-induced platelet aggregation between groups was abolished in the presence of a high concentration of the specific thromboxane antagonist ICI 192605, but not by prior incubation of blood with aspirin. Platelets from pregnant women were significantly less sensitive to inhibition of arachidonic acid induced activation by the thromboxane synthetase inhibitor dazmegrel, but there was no change in platelet cyclic AMP accumulation under these conditions. Arachidonic acid induced platelet thromboxane B2 production was similar in pregnant and non-pregnant subjects. In conclusion, platelets are more sensitive to the activating effects of thromboxane during pregnancy, but there is no change in the intrinsic reactivity of the thromboxane biosynthetic pathway.